The Importance of the Therapeutic Care Plan in Colorectal Surgery - Figueiredo, Henrique Carvalho e Silva; Corrêa Neto, Isaac José Felippe; Mocerino, Jéssica; de Oliveira, Mariana Campello; Robles, Laercio (Journal of Coloproctology, 2021)
Introduction A therapeutic plan is elaborated based on the health needs of each user, allowing a multidisciplinary team to assess diagnoses, treatment options, bonds, and optimal hospitalization time.Objectives To identify risk management tools already used and implemented in a reference teaching hospital in the city of São Paulo and to analyze their application and risk factors in medium and large colorectal surgery.Method Observational, longitudinal, and prospective study, with 30 patients with colorectal disease hospitalized in the surgical ward of the coloproctology service and in need of surgical treatment. In the first group, the protocol was applied with the knowledge of the researcher only, and, in the second group, with the knowledge of both the researcher and the attending physicians.Results Sixty percent of the patients were female with a mean age of 60.93 years and body mass index (BMI) of 26.07 Kg/m2.After surgery, patients in the first group who did not receive venous thromboembolism (VTE) prophylaxis in the first 24 hours had an increased risk of having the event compared with those who returned to prophylaxis (p < 0.005), thus suggesting this prophylaxis was a protective factor against thromboembolic event (p = 0.006). This group also had a higher risk of hypoglycemia when no strict control was performed (p = 0.041).Conclusion The compliance to hospital protocols with application monitoring, notedly in teaching places with annual admission of resident physicians, is a fundamental part of the adequate care of the patient combined with the implementation of therapeutic plans.
Keywords: therapeutic plan; risk management; colorectal surgery